2002
DOI: 10.1039/b200716a
|View full text |Cite
|
Sign up to set email alerts
|

Phase synchronization of nonidentical chaotic electrochemical oscillators

Abstract: Experiments on two coupled chaotic electrochemical oscillators with different frequencies are presented. We consider two types of coupling. The first is imposed through a set of external resistors. The second arises from the potential drop in the electrolyte and generally depends on cell geometry and reaction rate. Phase synchronization is observed with the addition of weak coupling of both types. Along with the onset of phase synchronization an increase in the amplitude of the mean current oscillations occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…9,10 When concentrations (or reaction rates) in these units exhibit oscillatory behavior, the interactions can produce a wide array of synchronization related behaviors, e.g., periodic 4,11,12 and chaotic 13,14 synchronization, oscillator death, [15][16][17][18][19][20] collective synchronization, [21][22][23] dynamical clustering, [24][25][26] and quorum transition. 27 The synchronization behaviors have been observed in BelousovZhabotinsky (BZ) reaction, 3,4,12,13,15,28,29 pH oscillators, 30 and biochemical reaction 31 in coupled continuously fed, stirred tank reactors (CSTRs), in metal dissolution 21,24,25,[32][33][34][35][36][37] and electrocatalytic [38][39][40] reactions in electrochemical systems, in CO oxidation on heterogeneous catalysts, 41,42 and in BZ beads, 22,23,26,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 When concentrations (or reaction rates) in these units exhibit oscillatory behavior, the interactions can produce a wide array of synchronization related behaviors, e.g., periodic 4,11,12 and chaotic 13,14 synchronization, oscillator death, [15][16][17][18][19][20] collective synchronization, [21][22][23] dynamical clustering, [24][25][26] and quorum transition. 27 The synchronization behaviors have been observed in BelousovZhabotinsky (BZ) reaction, 3,4,12,13,15,28,29 pH oscillators, 30 and biochemical reaction 31 in coupled continuously fed, stirred tank reactors (CSTRs), in metal dissolution 21,24,25,[32][33][34][35][36][37] and electrocatalytic [38][39][40] reactions in electrochemical systems, in CO oxidation on heterogeneous catalysts, 41,42 and in BZ beads, 22,23,26,…”
Section: Introductionmentioning
confidence: 99%
“…11 In most studies, symmetrical coupling effects were shown to induce in-phase, anti-phase, and fractured (slow adjustment of phases to in-and anti-phase configurations in a population) synchronization 11,25,,34-36,38,57 and amplitude death 16 of periodic oscillators. With chaotic oscillators coupling can induce bounded phase difference, functional mapping of the attractors, identical variation with time delay, and identical variations in phase, 32 generalized, 58 lag, 33 and identical 14 synchronization, respectively. The coupling in these examples was typically induced either by a potential drop in the electrolyte or by resistors attached to the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed characterization of the synchronization of two nonidentical Zn electrodes, for example, by studying time variation of a so called similarity function [20] or investigating changes in the Shannon entropy of the cyclic phase difference distribution as a function of the coupling strength [10] will be the subject of further research. In case of a large array of oscillators of S-NDR type, we plan to further look into the oscillatory variation of the average order parameter, and the distribution of the average phase shift of oscillators with respect to a reference one.…”
Section: Discussionmentioning
confidence: 99%
“…NDR type oscillators are further grouped into N-NDR and S-NDR type systems where N and S refer to the characteristic shape of the polarization curve [8,9]. Kiss et al [7,10] studied the effect of global coupling on the dynamics of interacting electrochemical oscillators of N-NDR type (electrodissolution of Ni) where the double-layer potential acts as a positive feedback variable. Here, we report on the effect of global coupling on the dynamics of interacting electrochemical oscillators of S-NDR type where the electrode potential acts as an essential negative feedback variable.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic behavior of some metals at the transition region from the active state to the passive state, from steady state to simple, double or chaotic oscillations, affords a large area of research interest in corrosion and protection of metals as well as understanding the oscillatory phenomena which occur at the solid/liquid interface processes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%